2022
DOI: 10.3390/ijerph191710662
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Mental Interventions among Youth Athletes: A Systematic Review and Meta-Analysis of the Studies

Abstract: (1) Background: The subject of athlete burnout is often discussed among sports psychologists. Interventions to reduce this phenomenon are still under investigation with follow-ups. Thus, the purpose of the current meta-analysis is to examine psychological interventions that was carried out to decrease or eliminate burnout syndrome in young athletes. (2) Methods: Scientific electronic databases were searched, and five published studies published between January and June 2022 that met the criteria were selected.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Additionally, acceptance-based intervention techniques are used to raise athletes’ performance levels, demonstrating the value of improving athletes’ flow state experiences in the context of sports [ 57 , 62 , 63 , 64 ]. Furthermore, mindfulness training might enhance athletes’ sporting experiences while also providing psychological benefits [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, acceptance-based intervention techniques are used to raise athletes’ performance levels, demonstrating the value of improving athletes’ flow state experiences in the context of sports [ 57 , 62 , 63 , 64 ]. Furthermore, mindfulness training might enhance athletes’ sporting experiences while also providing psychological benefits [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the area, however, with by far the least empirical support. For example, a recent review of interventions in sport [61] found only five studies that had used psychological interventions to prevent or reduce burnout in athletes. In addition, it was identified that the majority of these studies were at a moderate-to-high risk of bias due to several methodological issues (e.g., group allocation).…”
Section: Issue 5: Developing Effective Interventionsmentioning
confidence: 99%
“…Burnout is frequently accompanied by high levels of stress, a sense of loss of control, and mental and physical tiredness [ 11 ]. The transition from overreaching to overtraining to burnout is a complex phenomenon that involves a gradual shift from a normal and adaptive response to training to a maladaptive state of physical and psychological fatigue, with the negative effects on performance, health, and well-being becoming more severe and lasting [ 12 ].…”
Section: Introductionmentioning
confidence: 99%